2011
DOI: 10.1007/s00442-011-2229-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of extinction in fragmented plant populations: Crepis sancta (asteraceae) in urban environments

Abstract: Local populations are subject to recurrent extinctions, and small populations are particularly prone to extinction. Both demographic (stochasticity and the Allee effect) and genetic factors (drift load and inbreeding depression) potentially affect extinction. In fragmented populations, regular dispersal may boost population sizes (demographic rescue effect) or/and reduce the local inbreeding level and genetic drift (genetic rescue effect), which can affect extinction risks. We studied extinction processes in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…Finally, the low selfing rates found in the two networks are congruent with those obtained in the same populations based on multilocus heterozygosity (Dornier and Cheptou, 2012).…”
Section: Dispersal Processes In Plant Metapopulationssupporting
confidence: 84%
See 1 more Smart Citation
“…Finally, the low selfing rates found in the two networks are congruent with those obtained in the same populations based on multilocus heterozygosity (Dornier and Cheptou, 2012).…”
Section: Dispersal Processes In Plant Metapopulationssupporting
confidence: 84%
“…In our study, we controlled for the presence of null alleles using the XN data set for the JC network and our results suggested that immigration rate was indeed inflated by the presence of null alleles. Although such results were not obtained for the HM network, it is likely that the presence of null alleles biased estimates in the same way for the two networks, given the absence of significant genetic structure among the networks (Dornier and Cheptou, 2012). Although changing the genetic data set for JC was found to affect immigration, the immigration rate remained relatively high and was unlikely to be due to human error or marker quality.…”
Section: Immigration Rates In Plant Metapopulationsmentioning
confidence: 84%
“…We used eight neutral microsatellite markers [36,41] to assess levels of neutral genetic diversity within each population and between the fragmented and unfragmented (and urban and rural) sets of populations. We extracted DNA using maternal leaf tissue from 28-30 individuals per population using QIAGEN DNeasy Plant Mini kits.…”
Section: (D) Molecular Neutral Genetic Variationmentioning
confidence: 99%
“…Despite the importance of understanding the relative roles of demography and genetic processes for developing sound conservation decisions, experimental tests of these processes in nature are still sparse. Correlations between population size, heterozygosity, life history features, and local extinction have been observed (Pimm et al 1988, Saccheri et al 1998, Saether et al 2005, Dournier and Cheptou 2012, and experiments provide evidence that some of the mechanisms associated with small population size affect short-term components of population fitness (Jime´nez et al 1994, Newman and Pilson 1997, Madsen et al 1999, Nieminen et al 2001). However, we lack experimental information on the relative importance of different processes on long-term population dynamics and persistence.…”
Section: Introductionmentioning
confidence: 96%